A Study on the Influence of Stock Broker on Investor's Decision Making with Special Reference to Bombay Stock Exchange - Prabhakar Rajkumar, K.; Lakshmi Kavitha, N. (Indian Journal of Research in Capital Markets, 2017)
An investor is the backbone of the securities market in any economy. In the past, investments were confined to the rich class, but these days, investments are very popular among all groups of retail investors. The basic objective of individual investors who buy and sell securities is to get good returns on their investments. There are different factors that influence the investment decision of investors, for example, returns, capital appreciation, safety, liquidity, tax benefits, etc. Of a population of over one billion, barely 18 million invest in Indian equity markets. According to SEBI data, 10 cities contributed over 80% of the trading volume. Nowadays, online stock trading creates worldwide investment opportunities, and as an investor, everything can be understood with the help of a stockbroker. Also, a stockbroker helps investors to take decisions concerned with investment and management of their investments. The pattern of investment differs from investor to investor and is influenced by various factors. With this background, this study was conducted to highlight the dependency level of equity investors on stockbrokers for their investment decisions in the stock market. It brought to light the behaviour of equity investors and services received from stock brokers. For this study, primary data was used to identify the dependency level and services of stock brokers.